Genome Editing Gen ACO6 Exon 1-Genome 42 Pengkode Enzim Pensintesa Etilen Pada Tanaman Tomat (Solanum Lycopersicum L.) Berbasis Crispr/CAS9 Untuk Meningkatkan Umur Simpan Buah - Firsty Ayundia Hanun Pangisti (Fakultas Pertanian, 2026)
Ethylene is a plant hormone regulates the ripening process of climacteric fruits such as tomato. ACO6 (1-aminocyclopropane-1-carboxylic acid oxidase 6) belongs to the ACO family and plays a key role in the final stage of ethylene biosynthesis by converting ACC (1-aminocyclopropane-1-carboxylic acid) into ethylene. High ethylene accumulation in fruit can accelerate the ripening process, thereby shortening the shelf life of tomatoes. This study employed the CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 9) genome editing system mediated by Agrobacterium tumefaciens strain GV3101 carrying the plasmid construct pRGEB32::ACO6 to knock out the ACO6 gene targeted by sgRNA (single guide RNA) 2 through genetic transformation in cotyledon and apical shoot explants of the tomato variety Citra Asia. The research was conducted at the Agrobiotechnology Laboratory, Faculty of Agriculture, University of Jember. The results showed successful plant regeneration, with an average regeneration rate of 64.7% in apical shoot explants and 62.1% in cotyledon explants, and the acquisition of three positive transformant plantlets through hygromycin selection. These transformants were confirmed by PCR (Polymerase Chain Reaction) analysis using hptII (hygromycin phosphotransferase), sgRNA ACO6 sgRNA 2-specific, and Cas9 primers.
Validasi dan Finalisasi oleh Ratna 15 Juni 2026
Keywords: Transformation; ACO6; Ethylene; Tomato; Genome Editing; CRISPR/Cas9; Life span